Potential Antibacterial Activity of Bergenia purpurascens - Bajracharya, Gan B; Maharjan, Rokesh; Maharjan, Bijaya L (Nepal Journal of Science and Technology, 2012)
Bergenia purpurascens, an important traditional medicinal plant used as Ayurveda, was collected at 3800 m from the Manaslu Conservation Area. In vitro evaluation of the crude extracts of the plant rhizomes using agar well diffusion assay against eight bacteria displayed potential antibacterial activity. The minimum inhibitory concentration values for Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella paratyphi, Salmonella typhi, Salmonella typhimurium, Shiegella flexneri and Staphylococcus aureus were determined. This study supports the traditional use of the plant material for the healing of wounds and antibiotic effect. DOI: http://dx.doi.org/10.3126/njst.v12i0.6494 Nepal Journal of Science and Technology 12 (2011) 157-162